Dried ballonflower peeling and cutting equipment and use method - FENG YONGXING; SU LIANBO; HOU MIN (2024)
The invention relates to the technical field of dried ballonflower processing equipment, in particular to dried ballonflower peeling and cutting equipment and a using method thereof.The dried ballonflower peeling and cutting equipment comprises a bottom plate, and a plurality of driving structures are arranged at the top end of the bottom plate; the partition plate is fixedly installed at the top end of the bottom plate through a supporting frame, one side of the top end of the partition plate is rotationally connected with two sets of rotating supporting strips, the other side of the top end of the partition plate is provided with two sets of arc sliding grooves with the corresponding rotating supporting strips as the circle centers, and deflection supporting strips are arranged at the arc sliding grooves in a sliding mode. In the actual use process, ivy mosses screening is effectively controlled, the falling state of the ivy mosses is controlled, follow-up operation is facilitated, the screened ivy mosses c